Menggali Potensi Optimal Anak Usia Dini: Tinjauan Literatur - Komari Komari; Aslan Aslan (Jurnal Ilmiah Edukatif, 2025)
The strategy of exploring the optimal potential of early childhood involves a holistic approach that includes physical, cognitive, emotional, and social aspects. These strategies include providing developmentally appropriate stimulation through educational play activities, supporting exploration and creativity, and building positive interactions between the child and the environment. It is also important to create a safe and supportive environment, provide balanced nutrition, and ensure strong emotional support. An individualised approach that takes into account each child's unique needs and interests helps maximise their optimal development. The study in this research uses the literature method. The results showed that Genetic factors, stimulative environment, good nutrition, and psychosocial support were identified as key elements that contribute to child development. Genetic factors provide the biological foundation for growth and development, but full potential can be realised through positive interactions with the environment. An environment rich in stimulants and diverse learning experiences, as well as adequate nutrition play an important role in optimal cognitive and physical development. In addition, families play a crucial role in providing emotional and social support for children's development. Through a holistic approach that considers these various factors, parents and caregivers can help children achieve optimal development in the early years, which will lay the foundation for future development. The results of this review emphasise the importance of multi-faceted involvement in the early childhood care and education process to ensure the achievement of their full potential.